Assessment of dyslipidemia and its association with Type 2 Diabetes Mellitus in Bangladeshi subjects (Northern International Medical College Journal, 2022)
Background : Globally incidence of Type 2 Diabetes Mellitus (T2DM) shows an upward trend which a challenge for physicians and public health specialists. Patients with T2DM have 2- 4-fold increased risk of coronary artery disease (CAD), the leading cause of death among people with T2DM. Dyslipidemia considered an important factor for cardiovascular complication of T2DM.Objective : Assessment of dyslipidemia and its association with T2DM in Bangladeshi subjects.Methods : A case control study was conducted in CARe Medical College Hospital, Dhaka, during the period of July 2018 to June 2019. A total 153 subjects were included in study of which 90 belonged to Group-I were T2DM and 63 subjects were healthy Controls in Group-II. The Fasting glucose, postprandial glucose. Serum Lipid Profile were assayed in patients and controls, using standardized assay methods. Data were analyzed by using SPSS version 21.Results : Fasting plasma glucose levels [mmol/l, (Mean± SD)] of the study group were Control (4.96 ± 0.76) and T2DM (8.27±2.19) difference was statistically significant (p